1993
DOI: 10.1093/oxfordjournals.annonc.a058419
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of taxol (NSC-125973) in human ovarian carcinomas growing in the peritoneal cavity of nude mice

Abstract: The therapeutic activity against ovarian carcinoma xenografts supports the potential of taxol in the treatment of this neoplasia and forms the basis for future investigations aimed at optimizing the therapeutic activity of taxol given alone or in combination with other drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 9 publications
1
11
1
Order By: Relevance
“…However, data obtained from testing of paclitaxel in other tumor models support our prediction: paclitaxel was effective in preclinical testing against the human tumors CX-1 (colon), A431 (vulva), and FaDu (hypopharynx), when xenografted into nude mice (16,31,32), all of which are documented to contain p53 mutations (33,34). Additionally, paclitaxel was effective against numerous other tumor xenografts (31,32,50,51), few of which have been screened for their p53 status but at least some of which are likely to contain mutated p53.…”
Section: Discussionsupporting
confidence: 60%
“…However, data obtained from testing of paclitaxel in other tumor models support our prediction: paclitaxel was effective in preclinical testing against the human tumors CX-1 (colon), A431 (vulva), and FaDu (hypopharynx), when xenografted into nude mice (16,31,32), all of which are documented to contain p53 mutations (33,34). Additionally, paclitaxel was effective against numerous other tumor xenografts (31,32,50,51), few of which have been screened for their p53 status but at least some of which are likely to contain mutated p53.…”
Section: Discussionsupporting
confidence: 60%
“…Our results confirmed that CS5931 significantly inhibited angiogenesis both in vitro and in vivo . Cisplatin, a cytoxic antineoplastic drug, can inhibit endothelial cell proliferation in vitro but not affect angiogenesis in vivo [24,25,26,27], implying that drugs affecting endothelial cell proliferation are not necessarily anti-angiogenic. Our study revealed that the polypeptide also affected the growth of SIVs in zebrafish embryos.…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19][20] When tested with mammalian cells in culture, this substance showed general toxicity, with the exception of KB-V1 cells, which were resistant ( (Table 3). With KB cells ( Figure 2A), relative to the phosphate-buffered saline (PBS) control, paclitaxel treatment caused 70.2-85.3% growth inhibition at the i.p.…”
Section: Resultsmentioning
confidence: 99%